Antibacterial activity and retained protein of earthworm meal (Lumbricus rubellus) as feed additive combined with chitosan - Ahmad Sofyan; Ema Damayanti; Hardi Julendra (Indonesian Center for Animal Research and Development (ICARD), 2008)
This research was conducted to enhance the bacterial growth inhibition of E. coli by using earthworm (Lumbricus rubellus) meal (TCT) which was added with chitosan and its effect on the retained protein in broilers. Inhibition of E. coli growth was tested using dilution method on the nutrient broth by additional 2% TCT combined with 0, 0.5, 1.0 and 1.5% chitosan. Retained protein was measured using broiler fed diet containing 2% TCT (w/w) and added by chitosan 0, 0.5, 1.0 and 1.50% of TCT (w/w). The numbers of 15 broilers Cobb strain 35 days old were arranged on Completely Randomized Design (CRD). Results showed inhibition of E. coli was increased using TCT mixed chitosan. The highest inhibition to E. coli growth obtained from TCT + 0.5% chitosan. Retained protein tended to increase up to 1% (w/w) chitosan. Otherwise, chitosan level more than 1% could reduce protein retention. It is concluded that use of 1% chitosan increased TCT capability to inhibit E. coli and protein retention in the broilers. Key Words: Feed Additive, Chitosan, L. rubellus, E. coli